Answer:
For The value of a = 0 and c = 0 , The given expression equality is true
Step-by-step explanation:
Given expression as :
= a - 2
Or, 3 a² + ac + 2 c - 6 a = ( a - 2 ) × ( 3 a - c )
Or, 3 a² + ac + 2 c - 6 a = 3 a² - ac - 6 a + 2 c
Or, ( 3 a² + ac + 2 c - 6 a ) - ( 3 a² - ac - 6 a + 2 c ) =0
Or, ( 3 a² - 3 a² ) + ( ac + ac ) + ( 2 c - 2 c ) + ( - 6 a + 6 a ) = 0
or, 0 + 2 ac + 0
Or, 2 ac = 0
∴ a =0 and c = 0
Hence For The value of a = 0 and c = 0 , The given expression equality is true . Answer
Answer:
X=36
Step-by-step explanation:
90-54=36
Right angle 90 subtract 54
The missing angle x is 36
Answer: 125
Step-by-step explanation:
25% of 100 = 25
25 + 100
125
Answer:
P = 2(n - 6) + 2(n^2 - 8)
Step-by-step explanation:
Remembering that Area = Length times Width, we factor the given function
A = n^3 - 6n^2 - 8n + 48 in the expectation that the resulting factors represent the length and width respectively:
A = n^3 - 6n^2 - 8n + 48 factors as follows:
A = n^2(n - 6) - 8(n - 6), or A = (n - 6)(n^2 - 8)
We can label '(n - 6)' "width" and '(n^2 - 8'
length.
Then the perimeter, P, of the rectangle is P = 2(length) + 2(width). which works out here to:
P = 2(n - 6) + 2(n^2 - 8)
Multiply the numerator and denominator by the whole number. you'll most likely get an improper fraction though.